THE EFFECT OF GUIDED INQUIRY ASSISTED BY INTERACTIVE MULTIMEDIA ON SCIENTIFIC LITERACY SKILLS VIEWED FROM LEARNING MOTIVATION - Kantiti, Renny Indah; Sarkadi, Sarkadi; Sekarwinahyu, Mestika (Universitas Pakuan, 2023)
The research aims to examine differences in scientific literacy abilities in guided inquiry assisted by interactive multimedia and conventional learning; differences in students' learning motivation in the high and low categories in scientific literacy abilities; interaction of student learning motivation and guided inquiry assisted by interactive multimedia on scientific literacy abilities. The experimental method uses a 2X2 (AXB) design. The population of class V students was sampled using purposive sampling, 2 classes as a control group and an experimental group. Data collection techniques use questionnaires and tests and data analysis uses two-way analysis of variance. It can be concluded that there are differences in the scientific literacy abilities of guided inquiry assisted by interactive multimedia and conventional learning; there is no difference in the learning motivation of students in the high and low categories regarding scientific literacy abilities; and there is an interaction effect of student learning motivation and guided inquiry assisted by interactive multimedia on scientific literacy abilities. Students who have high learning motivation have better scientific literacy skills than students with low learning motivation. The results of this research can be used as material for teachers to consider in implementing learning innovations and alternative solutions to improve students' scientific literacy skills.